The Relationship Between Job Satisfaction and Organizational Commitment with Work Discipline in Banshu Electric Indonesia Employees - Susanti, Yulisa; Purba, Novia Sri Parindu; Ivania, Princilla Felisha (Indonesian Scientific Publication, 2024)
Industry is the root of the economy in a country. The study of job satisfaction, organizational commitment, and work discipline is critical to understanding their impact on individual well-being and workplace productivity. Job satisfaction refers to the level of happiness felt by employees towards their work, organizational commitment involves full dedication to the organization, and work discipline includes focus, regularity, and motivation in performing tasks. Understanding these factors can help organizations support employees in achieving a healthy work-life balance and improving work performance. The approach used in this research is a quantitative approach. The data collection technique used in this study is to use a Likert scale model. Based on this research, it is found that job satisfaction and organizational commitment have a significant correlation with work discipline in employees at Banshu Electric Indonesia. Overall, the results of this study can provide a prediction of employee discipline at Banshu Electric Indonesia which is quite large at 63.9%, while the remaining 36.1% is influenced by other factors not examined. For this reason, further research needs to be carried out to see other variables that are thought to have an effect in addition to the variables studied, such as exemplary leadership in the company, the size of compensation, threats, and definite rules from the company.